Assessment of liver ischemia reperfusion injury in mice using hepatic T2 mapping: Comparison with histopathology. Issue 6 (2nd May 2018) - Hueper, Katja; Lang, Hannah; Hartleben, Björn; Gutberlet, Marcel; Derlin, Thorsten; Getzin, Tobias; Chen, Rongjun; Abou‐Rebyeh, Hassan; Lehner, Frank; Meier, Martin; Haller, Hermann; Wacker, Frank; et al.
Abstract : Background: Liver ischemia reperfusion injury (IRI) occurs during liver surgery or transplantation resulting in an inflammatory response, tissue damage, and functional impairment of the organ. Purpose: To assess the feasibility of T2 mapping for noninvasive quantification of liver edema after partial liver IRI in mice. Study Type: Prospective, experimental study. Animal Model: Partial liver IRI was induced in C57BL/6‐mice by transient clamping of the left lateral and median liver lobes for 35 ( n = 8), 45 ( n = 6), 60 ( n = 17), or 90 minutes ( n = 5). For comparison, healthy C57BL/6‐mice were examined as controls ( n = 9). Field Strength/Sequence: Functional liver MRI was performed on a 7T scanner using a respiratory‐triggered multiecho spin‐echo sequence. Assessment: Healthy control mice and mice with partial liver IRI on day 1 after surgery, and additionally on day 7 in a subgroup with 60 minutes IRI ( n = 8) were examined. Maps of T2 relaxation time of liver tissue were used to assess distribution, severity of tissue edema (mean T2 time), and the percentage of edematous liver tissue. Statistical Test: One‐way analysis of variance (ANOVA) with Tukey's honest significant difference (HSD), paired t ‐tests, Pearson's test for correlation of MRI parameters with levels of liver enzymes, and histopathology, receiver operating characteristic (ROC) analysis. Results: Significant tissue edema induced by liver IRI as compared to the control group was detected by increased mean T2 times in groups with 60 minutes ( P < 0.001) and 90 minutes IRI ( P < 0.001). The percentage of edematous liver tissue significantly increased with longer ischemia times (controls 3.4 ± 0.4%, 35 minutes 5.3 ± 0.6%, 45 minutes 23.3 ± 7.6%, 60 minutes 39.7 ± 3.6%, 90 minutes 51.3 ± 4.5%). Mean T2 times and the percentage of edematous liver tissue significantly correlated with elevation of liver enzymes ( P < 0.001), histological evidence of liver injury ( r = 0.80 and r = 0.82, P < 0.001), and neutrophil infiltration ( r = 0.70 and r = 0.74, P < 0.001). In the subgroup with follow‐up, the severity ( P < 0.01) and extent of liver edema decreased significantly over time ( P < 0.01). Data Conclusion: T2 mapping allows quantification and follow‐up of liver injury in mice. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:1586–1594